Elemental analysis of agriculture soil by a pulsed carbon dioxide (CO2) Laser Induced Breakdown Spectroscopy (LIBS). (June 2020) - Idris, N; Susilayani, D; Sari, A M; Lahna, K; Ramli, M; Kurihara, K; Marwan
Abstract: Quick qualitative elemental analysis of agriculture soil has been made using a pulsed CO2 LIBS. The laser beam with different pulse energy was focused on agriculture soil sample under ambient of helium at atmospheric pressure (760 Torr) after the laser beam passes through a covering metal mesh. Emission spectra from the consequent plasma was recorded in wavelength range from 200 nm to 800 nm. It was found that by utilizing the mesh, intense plasma was generated immediately after the CO2 laser irradiation. It was seen that emission lines belong to salts, namely Ca, Mg, Na, K and metals such as Al, Si, Fe, Ti, Cr can certainly be identified. It was also found that the profile of the emission spectrum detected are basically relative similar to the standard soil, nevertheless the agriculture soil color is very different from the standard soil. Higher resolution and sensitivity optical multichannel analyzer (OMA) system is required to evaluate in greater detail the elemental composition of the soil samples.